Forms of Using the Internet to Support Student Activities in Online Classroom Learning in Higher Education - Mardiana, Puja Dikusuma; Sabiruddin, Sabiruddin; Gustia, Arifah Yenni; Yenis, Muhammad; Langputeh, Sukree (International Journal of Islamic Studies Higher Education, 2022)
One of the adjustments made in the learning process during the Covid-19 pandemic was the use of internet media.  With the presence of the internet as a source of information, it is very possible for someone to search for and disseminate all science and technology including writing inventions throughout the world easily, quickly, and cheaply.  The purpose of this study was to find out how the use of internet media and the role of internet media on student achievement majoring in Islamic Broadcasting Communication at Imam Bonjol State Islamic University, Padang.  This study uses a qualitative research method with a phenomenological approach, data sources are taken through in-depth interviews with thirty informants.  All data were analyzed thematically using the Miles and Huberman technique.  Mass Communication Theory which is used in this research is Uses and Gratificition Theory.  The results of the study found five activities carried out by students on the internet to support lectures: (i) looking for assignment references through journals, (ii) reading online news, (iii) watching Youtube tutorials, (iv) searching Google, Blogs, Web, (v) discuss and learn together like in a WhatsApp group.  Furthermore, overall, the informants stated that the use of the internet network could support their learning achievement in higher education.